A rare complication of capsule endoscopy, retained in diverticula: A report of two cases - Melissa Kyriakos Saad; Elias Fiani; Imad El Hajj; Elias Saikaly (Society of Gastrointestinal Intervention, 2021)
Capsule endoscopy is being widely used to identify the origin of an obscure gastrointestinal bleeding. Capsule retention is one of its complications. Herein, we present 2 cases of a retained capsule one in a gastric diverticula that was managed endoscopically, and one in jejunal diverticula managed by small bowel resection.